Language use among Malays in Kelantan / Nasuha Suhaili - Nasuha , Suhaili (2016)
This study looks at the different languages that are used in Kelantan and uncovers when certain languages are used in certain domains. It compares the use of language between the young and the old respondents and between gender groups. In addition, it also looks at the language attitudes of the respondents toward the Kelantanese Language and aims to gauge its overall vitality. A survey consisting of a 41-item questionnaire was used as a means to gather data for this research. The participants who responded were from three different age groups: young (14-21 years), mid (22-49 years) and older (50-80 years). A cross-sectional survey design was used while the data was tabulated using frequency counts, percentages, non-parametric Mann Whitney test and t-test. The findings reveal that the Kelantanese language is used in the majority of the domains, which shows that the language is very much vital. However, there is a definite shift in the younger group to using more standard forms. The female gender also showcases a preference to use more standard forms in the formal and social domains compared to the male gender. Furthermore, new social settings such as Facebook have widened the social circles of the younger generation, which inadvertently has promoted the use of English as a global language. It is the hope of the researcher that this research will add on to the body of knowledge pertaining to the current state of language use in Kelantan.